2015
DOI: 10.1044/2015_jslhr-s-14-0084
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions in Childhood Apraxia of Speech

Abstract: These results suggest that CAS involves a symptom complex that not only comprises errors of sequencing speech movements but implicates comorbidity in nonverbal sequential functioning in most children with CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 61 publications
(95 reference statements)
1
44
0
Order By: Relevance
“…There is considerably less agreement in both the CAS and AAS literatures on whether each disorder also includes deficits in representational processes-specifically, deficits in the precision and stability of encoding appropriately specified phonological representations of speech domains and/or deficits in memory constraining the storage and/or retrieval of representations (e.g., Chilosi et al, 2015;Nijland, Terband, & Maassen, 2015;Shriberg, Lohmeier, Strand, & Jakielski, 2012). Moreover, if deficits in appropriate specification and/or in the storage/retrieval of representations are documented in CAS, a significant question for theory and treatment is whether they are core or corollary deficits in the CAS phenotype.…”
Section: Representational and Transcoding Processing Deficits In Casmentioning
confidence: 99%
“…There is considerably less agreement in both the CAS and AAS literatures on whether each disorder also includes deficits in representational processes-specifically, deficits in the precision and stability of encoding appropriately specified phonological representations of speech domains and/or deficits in memory constraining the storage and/or retrieval of representations (e.g., Chilosi et al, 2015;Nijland, Terband, & Maassen, 2015;Shriberg, Lohmeier, Strand, & Jakielski, 2012). Moreover, if deficits in appropriate specification and/or in the storage/retrieval of representations are documented in CAS, a significant question for theory and treatment is whether they are core or corollary deficits in the CAS phenotype.…”
Section: Representational and Transcoding Processing Deficits In Casmentioning
confidence: 99%
“…The results from the Sensory Profile Questionnaire were also compared with Kaufman Speech Praxis Test which revealed significant positive correlations between oral-motor apraxia, abnormal imitations of oral movements and abnormal repetition of simple phonemes compared with sensitivity. Nijland et al [16] found that complex sensorimotor and sequential tasks correlate significantly with the severity of the speech impairment in children with CAS indicating a comorbidity in nonverbal sequential functioning.…”
Section: Sensory Processing Functions In Children With Msdmentioning
confidence: 99%
“…Comorbidity studies highlight the relationship of MSDs with dysfunctional sensory processing, complex sensorimotor tasks and sequential motor learning tasks as well as fine motor problems [15][16][17]. Findings also suggest some common neural correlates of speech and fine motor functions [18].…”
Section: Introductionmentioning
confidence: 95%
“…Based on these premises, the Computer Articulation Instrument (CAI) was developed (Maassen et al, 2019). The CAI consists of a battery of speech production tasks and is based on a series of studies of Dutch children with developmental and acquired SSDs Nijland, Maassen, van der Meulen, Gabreëls, et al, 2003;Nijland, Terband, & Maassen, 2015;Thoonen, Maassen, Gabreels, & Schreuder, 1999;Thoonen, Maassen, Gabreëls, & Schreuder, 1994). The CAI has a modular structure and provides an interactive administration and scoring of four speech tasks.…”
mentioning
confidence: 99%